2019 IFIP/IEEE 27th International Conference on Very Large Scale Integration (VLSI-SoC) 2019
DOI: 10.1109/vlsi-soc.2019.8920348
|View full text |Cite
|
Sign up to set email alerts
|

A Hardware-based Framework for Secure Firmware Updates on Embedded Systems

Abstract: Firmware refers to device read-only resident code which includes microcode and macro-instruction-level routines. For Internet-of-Things (IoT) devices without an operating system, firmware includes all the necessary instructions on how such embedded systems operate and communicate. Thus, firmware updates are an essential part of device functionality. They provide the ability to patch vulnerabilities, address operational issues, and improve device reliability and performance during the lifetime of the system. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Our flexible framework demonstrates the ability to be reconfigured in terms of hardware components while also giving the ability to EDs to be deployed in-field without any secure enrollment phase or hardcoded secrets within the ED's non-volatile memory. Recent work has shown that PPUFs alongside other security primitives implemented on hardware could be utilized for secure firmware delivery to in-field devices [16]. However, the approach is not end-to-end secure as it lacks the communication handshake required for two-way authentication in a truly public-key -based fashion.…”
Section: Related Work and Comparison With Proposed Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Our flexible framework demonstrates the ability to be reconfigured in terms of hardware components while also giving the ability to EDs to be deployed in-field without any secure enrollment phase or hardcoded secrets within the ED's non-volatile memory. Recent work has shown that PPUFs alongside other security primitives implemented on hardware could be utilized for secure firmware delivery to in-field devices [16]. However, the approach is not end-to-end secure as it lacks the communication handshake required for two-way authentication in a truly public-key -based fashion.…”
Section: Related Work and Comparison With Proposed Approachmentioning
confidence: 99%
“…Also, the updating procedure must be initiated from the firmware vendor's side which is not considered good practice in OTA updates [2,27]. The work in [17] improves the firmware updating procedure proposed in [16] by introducing digital signatures, which allow the device to better authenticate the manufacturer. However, it still suffers from the aforementioned drawbacks.…”
Section: Related Work and Comparison With Proposed Approachmentioning
confidence: 99%
“…Firmware updates are transmitted from the manufacturer to the embedded device through an insecure channel. The proposed approach relies on hardware as a root-of-trust to attain high security levels and is motivated towards low-end embedded devices [19]. The framework is designed in a way that user intervention and device downtime are minimized.…”
Section: Insecure Channelmentioning
confidence: 99%
“…can utilize for remote firmware updates. We enhance our preliminary work on leveraging hardware primitives to deliver firmware updates [9], in order to provide an end-to-end secure and modular framework, incorporating two-way authentication handshakes, strong confidentiality guarantees, and protection mechanisms against a variety of possible attacks. Our proposed methodology provides significant advantages over existing PUF-based techniques used primarily for authentication purposes:…”
Section: B Contributionsmentioning
confidence: 99%